A New Design of Internal Model Controller for SISO and MIMO Systems - Mahmoud, Ines; Saidi, Imen (A New Design of Internal Model Controller for SISO and MIMO Systems, 2022)
The works presented in this book are focused on the study of the Internal Model Control (IMC) structure of continuous and discrete multivariable dynamical systems. The internal model control structure is known to be robust, allows to consider the effects of modeling errors and external disturbances. Its main advantages lie in the simplicity of synthesis of the corrector, its ease of implementation and the explicit adjustment of the robustness. As for the disadvantages of this structure, they mainly relate to its applicability, reserved for stable open-loop or stabilized systems, the controller designed in this case must also be stable and feasible. In this structure, the synthesis of the controller is reduced to a problem of building an inverse model of the system to be controlled. In addition, the perfect inversion of the exact model is often impossible to achieve, in this case in the case of nonlinear systems and when the model can present sub-models with non-minimum phase or presenting modeling delays or when the order of the numerator is lower than that of the denominator and in the case where the input number is greater than the output number. The controller synthesis approach by internal model proposed in this book is based on a specific inversion used at the LARA Laboratory in the case of square SISO and MIMO systems. This approach has been modified, in the first step, to be able to obtain a possible inversion of the model in the case of non-square MIMO systems. In the second step, for this class of non-square dynamical system, we will develop a model inversion method relating to the "virtual outputs" and "virtual inputs" approach. This inversion approach can be applied to both minimal and non-minimal phase delay MIMO systems. The obtained internal model controller is simple, has few tuning parameters, easy to implement in industrial processes and presents good control and robustness performances.